The secret of the five bugs - McKay, C. R. (writer of juvenile literature) (Power Coders., 2019)
The Power Coders visit Grace's dad at the local museum to see a bug exhibit and must use their skills to find a set of missing moths before a big gala. They learn the museum's website has been hacked and must use their coding skills to debug the website in order to save Grace's dad's job.